RANKL inhibits cell proliferation by regulating MALAT1 expression in a human osteoblastic cell line hFOB 1.19 - Che, W; Dong, Y; Quan, H-B (Cellular and Molecular Biology, 2015)
Receptor activator of NF-ÎºB ligand (RANKL), a TNF-related protein, is a key factor regulating bone metabolism. It has been well known that RANKL-mediated signaling regulates the formation, activation and survival of osteoclast in normal bone modeling and remodeling, and also plays an important role in a variety of pathologic conditions. However, there is no direct evidence about the effect of RANKL on osteoblast. Herein, we investigated whether RANKL had effect on cell proliferation in a normal human fetal osteoblastic cell line hFOB 1.19. MTT assay showed that RANKL inhibited hFOB 1.19 cells growth in a dose-dependent and time-dependent manner. Importantly, we found that RANKL induced the expression of a lncRNA, MALAT1, for the first time. Knockdown of RANK by siRNA blocked the induction of MALAT1 by RANKL. By infection with MALAT1 siRNA, MALAT1 knockdown reversed RANKL-induced cells growth inhibition and cell cycle arrest. In addition, MALAT1 also regulated OPG expression in hFOB 1.19 cells. In conclusion, RANKL, binding to its receptor RANK, inhibited cell proliferation via MALAT1 upregulation in osteoblast cells in vitro.